Impact of a COVID-19 National Lockdown on Integrated Care for Hypertension and HIV - Jeremy I. Schwartz; Martin Muddu; Isaac Kimera; Mary Mbuliro; Rebecca Ssennyonjo; Isaac Ssinabulya; Fred C. Semitala (Ubiquity Press, 2021)
Research Letter Introduction: Measures to limit the spread of COVID-19, such as movement restrictions, are anticipated to worsen outcomes for chronic conditions such as hypertension (HTN), in part due to decreased access to medicines. However, the actual impact of lockdowns on access to medicines and HTN control has not been reported. Between March 25 and June 30, 2020, the Government of Uganda instituted a nationwide lockdown. Health facilities remained open, however motor vehicle transportation was largely banned. In Ugandan public health facilities, HTN services are offered widely, however the availability of HTN medicines is generally low and inconsistent. In contrast, antiretrovirals for people with HIV (PWH) are free and consistently available at HIV clinics. We sought to evaluate the impact of the lockdown on access to medicines and clinical outcomes among a cohort of Ugandan patients with HTN and HIV.